Rock avalanche of Potrero de Levés" southern Sierras Pampeanas, Sierra Grande of San Luis, Argentina (32° 30'S lot.) - Gonzalez Diaz, E.F. (1997)
The first rock avalanche to be identified in the southern Sierras Pampeanas is described here and its origin analysed. It is located in the northern sector (Cordon El Realito) of the San Luis fault scarp, which marks the western slope of the Sierra Grande de San Luis. It is suggested that the avalanche was triggered by seismic schock, a hypothesis supported by the seismotectonic and geologic conditions of the region as well as by the records of historical seismicity and by the recognition of modern fractures, scarplets and springwater spots in the piedmont area. Several other geological factors also support this suggestion, such as joint density, main shear zone location, attitude of the internal structure of granitoids and other nearby gravitational movements. The primary landforms of the avalanche landscape strongly suggest that the event was a recent one. The estimated speed is about 190 km/hour. © 1997 Asociacón Geológica Argentina.